Penerapaan Pelatihan Assertive untuk Mengatasi Kecemasan Berbicara di Depan Kelas di SMA Negeri 5 Palopo - Taswin, Muhammad Taslim (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This study aims to examine the implication of Assertive training to overcome speaking anxiety in front of the class at SMA Negeri 5 Palopo. The approach used in this paper involves quantitative-based research. It is done by pre-experimental design and one group pre-test to post-test form. The samples are 30 students from the 12th grade. The result of this study indicates a decrease in typical number from the interval of 118.13 to 118 with the average number in the interval of 106-130, escalating to 60 is considered high and the average interval from 56-80 is known to be low. Therefore, it can be reasoned out that the implication of Assertive training can overcome students’ speaking anxiety that is performed in the class.